Aktualisasi Diri Remaja Dalam Novel Lan Asira Wahdi Karya Amal Ahmad Tha’amah: (Kajian Psikologi Sastra) - Zururi, Miftahullah Ilmy; Amsariah, Siti (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study analyzes the forms of adolescent self-actualization in the main character "Olla" in the novel Lan Asira Wahdi by Amal Ahmad Tha'amah. Lan Asira Wahdi is the first novel by Amal Ahmad Tha'amah, written in 2010 in Damascus, Syria. The main character "Olla" suffers from severe depression symptoms due to bullying at school. She wants to free herself from her depression symptoms by self-actualizing to achieve peace of mind. This research applies a descriptive-analytical method using the Humanistic Psychology approach, specifically Abraham Maslow's five hierarchies of human needs, to analyze the forms of self-actualization in the character "Olla". The results of this study show, first, that Olla successfully fulfills all her needs for self-actualization. The needs for security, love, and self-esteem are more dominant. This is due to the role of the mother character who is always faithful in helping Olla in the process of fulfilling her self-actualization needs. Second, 11 characteristics of adolescent self-actualization behavior are found in Olla's character, namely: (1) ability to observe reality in depth, (2) acceptance of self and others, (3) spontaneity, honesty and openness, (4) focus on goals and problems outside themselves, (5) independence and having principles, (6) appreciation of efforts made, (7) mystical or peak experiences, (8) social interest, (9) interpersonal relationships, (10) focus on goals and aspirations, and (11) creativity.